Prospects for Biocontrol of Vibrio parahaemolyticus Contamination in Blue Mussels (Mytilus edulus)—A Year-Long Study - Onarinde, Bukola A.; Dixon, Ronald A. (Frontiers in Microbiology, 2018)
Vibrio parahaemolyticus is an environmental organism normally found in subtropical estuarine environments which can cause seafood-related human infections. Clinical disease is associated with diagnostic presence of tdh and/or trh virulence genes and identification of these genes in our preliminary isolates from retail shellfish prompted a year-long surveillance of isolates from a temperate estuary in the north of England. The microbial and environmental analysis of 117 samples of mussels, seawater or sediment showed the presence of V. parahaemolyticus from mussels (100%) at all time-points throughout the year including the colder months although they were only recovered from 94.9% of seawater and 92.3% of sediment samples. Throughout the surveillance, 96 isolates were subjected to specific PCR for virulence genes and none tested positive for either. The common understanding that consuming poorly cooked mussels only represents a risk of infection during summer vacations therefore is challenged. Further investigations with V. parahaemolyticus using RAPD-PCR cluster analysis showed a genetically diverse population. There was no distinct clustering for ‘environmental’ or 'clinical reference strains although a wide variability and heterogeneity agreed with other reports. Continued surveillance of isolates to allay public health risks are justified since geographical distribution and composition of V. parahaemolyticus varies with future ocean warming and the potential of environmental strains to acquire virulence genes from pathogenic isolates. The prospects for intervention by phage-mediated biocontrol to reduce or eradicate V. parahaemolyticus in mussels was also investigated. Bacteriophages isolated from enriched samples collected from the river Humber were assessed for their ability to inhibit the growth of V. parahaemolyticus strains in-vitro and in-vivo (with live mussels). V. parahaemolyticus were significantly reduced in-vitro, by an average of 1 log - 2 log units and in-vivo, significant reduction of the organisms in mussels occurred in 3 replicate experimental tank set ups with a ‘phage cocktail’ containing 12 different phages. Our perspective biocontrol study suggests that a cocktail of specific phages targeted against strains of V. parahaemolyticus provides good evidence in an experimental setting of the valuable potential of phage as a decontamination agent in natural or industrial mussel processing.